2009
DOI: 10.1080/15459620903139060
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Hearing Protection Use: Self-Report and Researcher Observation

Abstract: Hearing protection devices (HPD) are commonly used to prevent occupational noise-induced hearing loss. There is a large body of research on hearing protection use in industry, and much of it relies on workers’ self-reported use of hearing protection. Based on previous studies in fixed industry, worker self-report has been accepted as an adequate and reliable tool to measure this behavior among workers in many industrial sectors. However, recent research indicates self-reported hearing protection use may not ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 27 publications
1
35
1
Order By: Relevance
“…However, we did attempt several methods of accounting for HPDs, including restricting the analysis to those that reported never using HPDs, which is most likely to be accurate, and found no significant change in our effect estimates. In our previous analyses of HPD use among construction workers, we have found 50% of construction workers self-reported ‘always’ use, but when observed, the fraction of exposure time in which HPDs were used was only about 17%37 to 24% 32…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, we did attempt several methods of accounting for HPDs, including restricting the analysis to those that reported never using HPDs, which is most likely to be accurate, and found no significant change in our effect estimates. In our previous analyses of HPD use among construction workers, we have found 50% of construction workers self-reported ‘always’ use, but when observed, the fraction of exposure time in which HPDs were used was only about 17%37 to 24% 32…”
Section: Discussionmentioning
confidence: 85%
“…The cohort included construction workers who have relatively high noise exposure levels, including a high degree of peak noise, but who wear HPDs a small fraction of the time 32. The analysis is based on an exposure measurement database of over 1300 full-shift personal noise dosimetry measurements on subjects and construction workers doing comparable work 30.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Self-reported HPE use may also vary with the type of noise exposure: variable or steady state. 34 For this study, we asked workers to report on their typical HPE use when working in noise, and did not specifically ask for information about the day that noise measurements were made. This may have led to higher than expected reported usage rates.…”
Section: Commentmentioning
confidence: 99%
“…If we stimulate bone conduction, their speech perception ability would be altered. According to Griffin et al's survey study, [17] workers in the steady noise environment self-reported the use of hearing protection more accurately than workers in variable noise environments. Third, almost all bone conduction studies have been conducted over the past 40 years, so the results have been limited to audiology applications, such as using a bone conduction device to measure the hearing threshold in order to differentiate middle-ear disorders from inner-ear disorders.…”
Section: Conclusion and Suggestionmentioning
confidence: 99%
“…[19] Moreover, voice type such as male or female and background noise levels should be considered in future studies. [18] Since chronic NIHL is most commonly caused by prolonged exposure to high levels of noise, to prevent manufacturing and construction workers from developing NIHL, [17] effective hearing protection devices and communicating though bone conduction must be used.…”
Section: Conclusion and Suggestionmentioning
confidence: 99%